Targeting the PI3K/Akt pathway for the treatment of ulcerative colitis: integrative regulatory features of traditional Chinese medicine - Niu, Siying; Zhang, Yang (Frontiers in Pharmacology, 2025)
The development of ulcerative colitis (UC), a highly prevalent inflammatory bowel disease worldwide, is closely related to the key regulatory role of the PI3K/Akt signaling pathway. Although the use of Western drugs is the standard clinical treatment, the problems of drug resistance, side effects, and efficacy limitations are prominent. In contrast, Traditional Chinese Medicine (TCM), with the advantages of multi-target regulation and low toxicity and side effects, demonstrates the potential for and offers highly effective treatment. This paper systematically analyzes the mechanism of the PI3K/Akt pathway in UC. It focuses on how TCM metabolites, extracts, and formulas regulate inflammatory responses, oxidative stress, autophagy and apoptosis, intestinal barrier function, and gut microbiota homeostasis by targeting the pathway, which together can achieve the goal of alleviating the symptoms of UC. Our goal is to provide new insights into the prevention and treatment of UC and to contribute to the standardization of TCM.